2002
DOI: 10.1159/000064916
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Farnesol and Xylitol against <i>Staphylococcus aureus</i>

Abstract: Background: Heavy colonization of atopic dermatitis (AD) with Staphylococcus aureus is well documented. The isolation rate of methicillin-resistant S. aureus is high in strains from AD in Japan. Our objective in the present study was to investigate the actions of farnesol and xylitol against S. aureus for the control of AD skin lesion-colonizing S. aureus.Methods: We examined the actions of farnesol on plasma coagulation and superantigenic exotoxin production by S. aureus, the antimicrobial activity of β-lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…In fact, exposure to terpene alcohols has been recently shown to affect the cell membranes of S. aureus, Escherichia coli, and Listeria monocytogenes, resulting in leakage of K ϩ ions from cells (2,7,22,24). However, the farnesol levels used in these experiments (Ͼ1 mM) were found to be inhibitory to S. aureus and therefore the effect of farnesol on S. aureus was not evaluated or investigated further at lower concentrations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, exposure to terpene alcohols has been recently shown to affect the cell membranes of S. aureus, Escherichia coli, and Listeria monocytogenes, resulting in leakage of K ϩ ions from cells (2,7,22,24). However, the farnesol levels used in these experiments (Ͼ1 mM) were found to be inhibitory to S. aureus and therefore the effect of farnesol on S. aureus was not evaluated or investigated further at lower concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of the biosynthesis of farnesyl pyrophosphate results in blocking of DNA synthesis and arrest of cell growth (12,21,30,32). Although the effect of farnesol on S. aureus has not been fully investigated, some studies have indicated a possible interaction of farnesol with cell membranes of certain bacterial species, including Streptococcus mutans (2,7,22,24,30). In S. mutans, for example, brief exposure to farnesol affected growth and metabolism by disrupting the bacterial membrane, as well as the accumulation and polysaccharide content of biofilms of the streptococci (24).…”
mentioning
confidence: 99%
“…An attractive idea to combat microbial biofilms could be to synergize old antibiotics with novel antimicrobial agents [17], and we are planning to study combinations between conventional antibiotics and the most active 4-diazopyrazoles against microbial biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…1), tannin shows both reducing and stabilizing properties and is commonly used for the synthesis of silver [4][5][6], gold [4,7] and nickel [8] nanoparticles. Moreover, it has been widely reported in the literature, that tannin exhibits natural antioxidant [9,10], antimicrobial [11][12][13] and antiviral activity [14,15]. As an antioxidant compound, tannin and its derivatives, especially gallic and pyrogallol, prevent lipid oxidation and radical-mediated DNA cleavage by scavenging oxygen and oxygen-derived radicals [10].…”
Section: Introductionmentioning
confidence: 99%